Growth and characterization of 2-amino-5-methylpyridinium phosphate crystals. (2022) - Nithya, S.; Chandar Shekar, B.; Aranganayagam, K.R.; Boopathi, K.
Abstract: Good-quality single crystals of 2- Amino-5-methylpyridinium phosphate (2A5MPP) have been grown by slow evaporation technique. The cell parameters of the grown crystals were studied and the crystal belongs to monoclinic structure with the space group P21 /n. FTIR spectral analyses were carried out in order to determine the functional groups. The UV–visible absorption spectra were recorded for the grown crystal. The nonlinear refractive index and third order susceptibility values of 2A5MPP crystal are estimated using a Z-scan technique.